Effect of climate change on soil organic carbon in Inner Mongolia. (14th March 2014) - Zhao, Dongsheng; Wu, Shaohong; Dai, Erfu; Yin, Yunhe
ABSTRACT This study simulated the response of soil organic carbon (SOC) to future climate change in Inner Mongolia. The Lund–Potsdam–Jena model, which is a dynamic vegetation model, was improved in accordance with the ecosystem features in China. In this study, this model was driven by the A1B, A2, and B2 climate scenarios generated by a regional climate model. To assess the spatial and temporal variations in SOC, four 30‐year periods were defined, namely baseline term (1961–1990), near term (2011–2040), middle term (2041–2070), and long term (2071–2100). Results suggest that, under the climate scenarios, soil organic carbon density (SOCD) significantly decreases from 1991 to 2100. SOCD may slightly decrease before 2025 but rapidly decreases after 2025, particularly for the A1B scenario, which shows the largest decrement in SOCD, followed by the B2 and A2 scenarios. Large and small decrements of SOCD may occur in Western and Eastern Inner Mongolia, respectively. The effects of climate change on SOCD are generally insignificant in the near term. In the middle term, the areas of SOCD decrement would expand, and the negative effects of climate change would dominate. In the long term, the negative effect of climate change would be further enhanced, and the SOCD in most areas of Inner Mongolia would decrease.